IFRS Adoption and the Financial Statements Comparability: The Case of Russia and Canada - Tatiana Dolgikh (European Financial and Accounting Journal, 2022)
The effect of International Financial Reporting Standards (IFRS) adoption on the level of financial statements comparability was investigated for Russia in the current article. Canada was chosen for comparison due to the close time frame of IFRS adoption, which also allowed comparing the influence of IFRS adoption for both types of economies - well developed and emerging. Initial sample selection had been created from 23 companies that are presented on the stock exchange markets of the particular countries. Each sample contains semi-annual data for four years of the pre-adoption period (2008 to 2011 for Russia, 2007 to 2010 for Canada) in which companies use their home country accounting standards and four years of the post-adoption period (2012 to 2015 for Russia, 2011 to 2014 for Canada) in which companies use IFRS standards. The research was performed on the country level and industry level for both countries. Two measures had been used for the research: earnings-return regression and earnings-cash flow regression. The overall result of the study shows that the application of IFRS improved information comparability between companies only in Canada, while the same was not the case for Russian companies and the cross-country comparability. However, the study confirms an increase in the comparability level in the post-adoption period in such industries as Energy and Basic materials not only between companies inside of the given country but on the cross-country level as well.
Keywords: M41; M42; 650; IFRS; Comparability; Russia; Canada